2018
DOI: 10.1002/hipo.22824
|View full text |Cite
|
Sign up to set email alerts
|

The content of hippocampal “replay”

Abstract: One of the most striking features of the hippocampal network is its ability to self-generate neuronal sequences representing temporally compressed, spatially coherent paths. These brief events, often termed "replay" in the scientific literature, are largely confined to non-exploratory states such as sleep or quiet rest. Early studies examining the content of replay noted a strong correlation between the encoded spatial information and the animal's prior behavior; thus, replay was initially hypothesized to play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
138
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(143 citation statements)
references
References 114 publications
(222 reference statements)
5
138
0
Order By: Relevance
“…The third is representational, and perhaps the most evocative. During SWRs, populations of place cells often fire in temporally compressed sequences reflecting spatial trajectories (example in Figure ; reviewed in O'Neill, Pleydell‐Bouverie, Dupret, & Csicsvari, ; Carr, Jadhav, & Frank, ; Buzsaki, ; Foster, ; Pfeiffer, ; Olafsdottir, Bush, & Barry, ). This sequential firing pattern, termed “replay sequences” or “replay,” has been shown to represent (a) spatial trajectories in both forward and reverse order (Csicsvari, O'Neill, Allen, & Senior, ; Davidson, Kloosterman, & Wilson, ; Diba & Buzsaki, ; Foster & Wilson, ; Gupta, van der Meer, Touretzky, & Redish, ), (b) spatial trajectories in locations or environments remote from the subjects (Davidson, Kloosterman, & Wilson, ; Gupta et al, ; Karlsson & Frank, ), (c) spatial trajectories in novel combinations not seen in prior behavior (Gupta et al, ), (4) spatial trajectories extending over meters (Davidson, Kloosterman, & Wilson, ), and (5) spatial trajectories taken by subjects in subsequent goal‐directed navigational behavior (Pfeiffer & Foster, ; see also Wu, Haggerty, Kemere, & Ji, ).…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%
See 3 more Smart Citations
“…The third is representational, and perhaps the most evocative. During SWRs, populations of place cells often fire in temporally compressed sequences reflecting spatial trajectories (example in Figure ; reviewed in O'Neill, Pleydell‐Bouverie, Dupret, & Csicsvari, ; Carr, Jadhav, & Frank, ; Buzsaki, ; Foster, ; Pfeiffer, ; Olafsdottir, Bush, & Barry, ). This sequential firing pattern, termed “replay sequences” or “replay,” has been shown to represent (a) spatial trajectories in both forward and reverse order (Csicsvari, O'Neill, Allen, & Senior, ; Davidson, Kloosterman, & Wilson, ; Diba & Buzsaki, ; Foster & Wilson, ; Gupta, van der Meer, Touretzky, & Redish, ), (b) spatial trajectories in locations or environments remote from the subjects (Davidson, Kloosterman, & Wilson, ; Gupta et al, ; Karlsson & Frank, ), (c) spatial trajectories in novel combinations not seen in prior behavior (Gupta et al, ), (4) spatial trajectories extending over meters (Davidson, Kloosterman, & Wilson, ), and (5) spatial trajectories taken by subjects in subsequent goal‐directed navigational behavior (Pfeiffer & Foster, ; see also Wu, Haggerty, Kemere, & Ji, ).…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%
“…One is that the distinction between localizing versus generative is expected to be most relevant in the awake and task‐engaged subject, for whom the appropriate synthesis of localizing and generative neural activity has short‐term consequences for the subject by way of upcoming behavior. The other is that theta sequences and replay sequences each have both localizing and generative properties (Buzsaki, ; Carr et al, ; Foster, ; Olafsdottir et al, ; Pfeiffer, ; Redish, ).…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have shown that post-learning neural processes play a critical role in consolidating new memories (Diekelmann & Born, 2010;McGaugh, 2000;Sasaki, Nanez, & Watanabe, 2010). One of the consolidation processes is the reemergence of the brain activities involved in the initial task during following wakefulness and sleep (Foster, 2017;Pfeiffer, 2017;Tambini & Davachi, 2019).…”
Section: Introductionmentioning
confidence: 99%